Endoscopic percutaneous repair of laryngeal cleft - Tang, XinYe; Yang, Yang; Zhang, ZhiHai; Sun, Rong (Frontiers in Pediatrics, 2023)
Objectives: The aim of this study was to describe a novel surgical technique of endoscopic percutaneous repair in pediatric patients with type 1, type 2 and type 3 laryngeal cleft (LC). Methods: A retrospective study involving 12 patients with LC was performed at a tertiary pediatric hospital from February 2021 to June 2022. All patients underwent endoscopic percutaneous repair. Information such as demographics, comorbidities, history of tracheostomy and the open approach for the repair, type of cleft and complications were analyzed. Results: A total of 12 patients were diagnosed with LC. The median age of the patients at the time of surgery was 8.50 months (IQR, 49.50 minutes). Seven patients had tracheomalacia, four patients had subglottic stenosis, three patients had laryngomalacia. There were no complications of surgery for 10 patients with a primary procedure. For 2 patients with a secondary procedure, the endoscopic percutaneous repair failed again to heal the cleft. During the follow-up period after surgery, none of the patients had stridor, recurrent pneumonia, difficulties during feeding or dyspnea. Follow-up MBS following surgery showed no aspiration in 10 patients. Only the 2 patients with a secondary procedure had intermittent cough while taking large gulps of water. The cure rate of endoscopic percutaneous repairer was 83.3% (95% confidence interval: 73.9%-92.8%). Conclusion: Endoscopic percutaneous repair should be considered as an alternative to the open transcervical approach and the traditional endoscopic approach for type 1, type 2 and type 3 LC.